Experimental Study on Electrochemical Corrosion Law of Rebar Under Alternating Magnetic Field - Yang, Jianyu; Ye, Xin; Yang, Weijun (Civil Engineering Journal, 2025)
The alternating magnetic field (MF) environment of coastal substations and magnetic levitation systems generates strong electromagnetic interference, which may affect the corrosion behavior of rebars in concrete structures. To clarify the influence law of rebar corrosion when exposed to an alternating MF, an alternating MF simulation test device was designed and manufactured according to the principle of alternating electromagnetic induction. The macroscopic corrosion morphology and electrochemical corrosion characteristics of rebars under alternating MF of different intensities were investigated by accelerated corrosion tests, electrochemical tests and natural corrosion electrochemical tests. The corrosion behavior mechanism of rebars under alternating MF was revealed. The results show that: 1) The diffusion rate and concentration of corrosion products in the solution are proportional to the magnetic induction strength. The alternating MF accelerates rebar corrosion. 2) The Ecorr of rebar shifts negatively with the magnetic induction strength increases, with a more pronounced shift in the early stage of corrosion than in the later stage. 3) Under the natural corrosion state, the 5 mT MF makes the open circuit potential (OCP) shift 12 mV negatively compared with that without MF. When the potential reaches 8mV, the passivation film begins to be destroyed. 4) The R1 of rebar is inversely proportional to the magnetic induction strength.